MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN MENULIS PESERTA DIDIK TUNARUNGU DI SEKOLAH LUAR BIASA - Nurhalimah, Isnaini (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: Impact of hearing impaired children in language development. The inhibition of language development has an impact on the development of intelligence, social and emotional, and personality. Because of such complex impacts, it is necessary to develop language skills. Therefore, in this study examines the contextual learning model on the ability to write students deaf in SMPLB-B Karya Mulia Surabaya.  The purpose of this study was to examine the effect of contextual learning model on the ability to write personal experiences of Deaf students at SMPLB-B Karya Mulia Surabaya. This research method uses quantitative approach and Pre Experiment research type, using research design of The One Group Pre-test Post-test Design to obtain data of writing ability before and after given treatment. The result of data analysis using Wilcoxon formula shows that there is a significant influence of the use of contextual learning model on the ability of writing deaf students in SMPLB-B Karya Mulia Surabaya Keywords: Contextual learning model, writing